Utility of the World Health Organization Disability Assessment Schedule and the World Health Organization minimal generic set of domains of functioning and health in spinal cord injury - Sinikka Tarvonen-Schröder; Anne Kaljonen; Katri Laimi (Medical Journals Sweden, 2018)
Objective: To compare easy-to-use International Classification of Functioning, Disability and Health (ICF)-based measures of functioning with the level and severity of spinal cord injury. Methods: Cross-sectional study. Patients (n = 142) and their significant others completed the 12-item World Health Organization Disability Assessment Schedule (WHODAS 2.0) questionnaire. A physician at the university hospital outpatient clinic assessed functioning with the 7-item World Health Organization (WHO) minimal generic set. Results: The patient and proxy WHODAS sum score was rated severe with decreasing severity in groups with complete and partial tetraplegia and paraplegia, respectively. Working ability was rated most severely impaired in the tetraplegic groups. Between-group differences were also found in mobility, household tasks, and self-care. Mobility was found to be associated with lesion severity; life activities, participation and friendships with lesion level; and self-care and WHODAS sum score with both lesion severity and level. Depending on the level and severity of spinal cord injury, a moderate to strong correlation was found between the sum scores of the 2 tools, and mostly very strong correlations between patient and proxy assessments of functioning. Conclusion: Both generic ICF-based tools, despite their briefness, seemed to be useful as they were able to differentiate various levels and severities of spinal cord injury. We recommend using the 12-item WHODAS 2.0 when planning individualized services for patients with spinal cord injury.